2014
DOI: 10.1093/jac/dku221
|View full text |Cite
|
Sign up to set email alerts
|

A single 2 g oral dose of extended-release azithromycin for treatment of gonococcal urethritis

Abstract: Objectives: We treated gonococcal urethritis in men with a single 2 g dose of azithromycin extended-release formulation (azithromycin-SR) to determine its microbiological outcomes and tolerability. Patients and methods:We enrolled 189 Japanese men with gonococcal urethritis between April 2009 and December 2013. The patients were given a single 2 g dose of azithromycin-SR. Microbiological efficacy was evaluated by the results of the post-treatment molecular testing of Neisseria gonorrhoeae. MIC testing was perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
12
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 19 publications
1
12
1
Order By: Relevance
“…A study recently conducted in Japan revealed that the eradication rate of N.gonorrhoeae isolates with azithromycin MICs of 0.5 mg/L or less was 98.9% (88/89) and that of the isolates with MICs of 1 to 4 mg/L was only 50.0% (7/14) in men with gonococcal urethritis treated with a single 2-g dose of azithromycin. 16 In the present study, a high proportion of azithromycin-resistant gonococci (22.6%; MIC > 0.5 mg/L) was observed in 2013.…”
Section: Discussionsupporting
confidence: 45%
“…A study recently conducted in Japan revealed that the eradication rate of N.gonorrhoeae isolates with azithromycin MICs of 0.5 mg/L or less was 98.9% (88/89) and that of the isolates with MICs of 1 to 4 mg/L was only 50.0% (7/14) in men with gonococcal urethritis treated with a single 2-g dose of azithromycin. 16 In the present study, a high proportion of azithromycin-resistant gonococci (22.6%; MIC > 0.5 mg/L) was observed in 2013.…”
Section: Discussionsupporting
confidence: 45%
“…Although descriptions of the effectiveness of AZM for the treatment of gonococcal urethritis have been added to the guidelines revised in 2016 (4), the decreasing susceptibility of N. gonorrhoeae to AZM has been reported in Japan (22,24). In our current study, the microbiological efficacy of a single 2-g dose of AZM-SR was 83.3%, which was lower than that previously reported (93.8%) (14). Additionally, gonococcal strains exhibiting high levels of AZM resistance (MICs Ն 256 mg/liter) have been reported in an increasing number of countries (10,11,(25)(26)(27).…”
Section: Discussioncontrasting
confidence: 70%
“…Although a single 2-g dose of an immediate-release formulation of AZM (conventional AZM) remains effective against uncomplicated gonorrhea (12), this monotherapy could cause an unacceptable rate of adverse events, particularly gastrointestinal upset. Recently, a single 2-g dose of a microsphere-based extended-release formulation of AZM (AZM-SR) was developed and was found to be effective against N. gonorrhoeae (13)(14)(15), and the frequency of adverse events also decreased compared with that achieved with a single 2-g dose of conventional AZM (12,(15)(16)(17)(18). Therefore, a single 2-g dose of AZM-SR is considered useful for the treatment of gonorrhea.…”
mentioning
confidence: 99%
“…Oral antibiotics for outpatient treatment would be highly desirable for this kind of infection. Azithromycin (AZM) is an oral antibiotic with medical insurance approval for use against chlamydia infections (14), and there are many reports of good activity against N. gonorrhoeae infection (15). Other reports suggest that N. gonorrhoeae infection is less susceptible to AZM and that AZM-resistant strains have emerged (5).…”
mentioning
confidence: 99%